2014
DOI: 10.1007/s13311-013-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dystonia

Abstract: Selecting the appropriate treatment for dystonia begins with proper classification of disease based on age, distribution, and underlying etiology. The therapies available for dystonia include oral medications, botulinum toxin, and surgical procedures. Oral medications are generally reserved for generalized and segmental dystonia. Botulinum toxin revolutionized the treatment of focal dystonia when it was introduced for therapeutic purposes in the 1980s. Surgical procedures are available for medication-refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 142 publications
0
51
0
1
Order By: Relevance
“…[9,36] This together with the severe disability typically caused by dystonia encourages the use of symptomatic treatments that are known to be effective in other neurodegenerative disorders manifested by dystonia. [24] The treatment of dystonia depends on its severity and localization. Independent of etiology, focal dystonias are usually treated with BTX injections.…”
Section: [32]mentioning
confidence: 99%
See 2 more Smart Citations
“…[9,36] This together with the severe disability typically caused by dystonia encourages the use of symptomatic treatments that are known to be effective in other neurodegenerative disorders manifested by dystonia. [24] The treatment of dystonia depends on its severity and localization. Independent of etiology, focal dystonias are usually treated with BTX injections.…”
Section: [32]mentioning
confidence: 99%
“…[6,24,27,37] The pharmacological agents used in the treatment of dystonia include (1) anticholinergics, (2) baclofen, (3) benzodiazepines, (4) dopaminergic compounds (levodopa or dopamine agonists), (5) dopamine-depleting drugs, and (6) antiepileptic drugs (carbamazepine/oxcarbamazepine). [24,28] The data on the efficacy of this kind of treatment in patients with WD are limited but encouraging. BTX injections used in focal dystonias were effective in 8/9 patients with WD (the remaining patient had a slight improvement), as reported separately by three different centers.…”
Section: [32]mentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence supports the hypothesis that anticholinergic therapy in patients prone to develop TD may increase the incidence of this disorder. Some studies however have shown improvement in tardive dystonia following trihexyphenidyl treatment [46,50].…”
Section: Anticholinergic Drugsmentioning
confidence: 99%
“…The impact of surgical approaches is also examined, but the conclusion remains that there is a need for new treatments. Thenganatt and Jankovic [12] provide a comprehensive review of therapeutic approaches for dystonia discussing the standard medications, as well as outcomes of clinical trials of chemodenervation with botulinum toxins and surgical techniques. The roles of these therapeutic interventions are discussed based on a new classification of disease.…”
mentioning
confidence: 99%